2019
DOI: 10.4041/kjod.2019.49.5.279
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of anchorage with temporary anchorage devices during anterior maxillary tooth retraction: A randomized clinical trial

Abstract: ObjectiveThis study evaluated the efficiency of anchorage provided by temporary anchorage devices (TADs) in maxillary bicuspid extraction cases during retraction of the anterior teeth using a fixed appliance.MethodsPatients aged 12 to 50 years with malocclusion for which bilateral first or second maxillary bicuspid extractions were indicated were included in the study and randomly allocated to the TAD or control groups. Retraction of the anterior teeth was achieved using skeletal anchorage in the TAD group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…One of the key components of orthodontic treatment is anchorage control. Many studies focused on linear change instead of on tipping movement of molars [14,15]; however, during orthodontic treatment, crown movement surpasses root movement in speed and extent, signifying the initiation of anchorage loss. Molar mesialization almost always accompanies forward tipping, in other words, mesial tipping is closely related to anchorage loss.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key components of orthodontic treatment is anchorage control. Many studies focused on linear change instead of on tipping movement of molars [14,15]; however, during orthodontic treatment, crown movement surpasses root movement in speed and extent, signifying the initiation of anchorage loss. Molar mesialization almost always accompanies forward tipping, in other words, mesial tipping is closely related to anchorage loss.…”
Section: Discussionmentioning
confidence: 99%
“…Mini implant orthodontic diketahui mampu memberikan penjangkaran yang stabil dan mencegah terjadinya anchorage loss pada fase penutupan ruang ekstraksi karena gigi posterior terbebas dari gaya dan momen yang terjadi. 6,9,10 Dilakukan retraksi anterior en masse dengan mekanika sliding menggunakan power chain ke piranti penjangkaran setelah tahap leveling dan aligning pada rahang atas selesai (Gambar 4). Mini implant orthodontic dapat digunakan sebagai penjangkaran langsung pada mekanisme penutupan ruang secara sliding mechanic 11,12 maupun non sliding mechanic.…”
Section: Pembahasanunclassified
“…However, several authors have demonstrated the efficacy of sectional appliances in conjunction with TADs in managing complex post-extraction space closure in the posterior sectors, stating that such an approach meets the demands of adult patients to be treated efficiently, aesthetically (without bulky, visible equipment), and with reduced need for compliance [10,11]. Although TADs cannot be considered entirely immovable during either the direct or indirect application of orthodontic forces [12], they certainly provide an adequate and satisfactory reinforcement of the anchorage [13] and these remain stable when correctly placed in the bone during tooth retraction and protraction phase [14]. The aim of this paper is to highlight how the careful use of skeletal anchorage and appropriate orthodontic biomechanics can yield satisfactory results in a reduced treatment time, even in complex cases.…”
Section: Introductionmentioning
confidence: 99%